2016
DOI: 10.1111/aas.12737
|View full text |Cite
|
Sign up to set email alerts
|

Manual vs. pressure-controlled facemask ventilation for anaesthetic induction in paralysed children: a randomised controlled trial

Abstract: Although PCV provided lower PAP than MV at the same tidal volume, the risk of GI may not be eliminated during facemask ventilation in paralysed small children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
4
17
0
Order By: Relevance
“…Our results were similar to those of previous studies that reported that 18-50% of cases of gastric insufflation detected by ultrasonography were missed when using epigastric auscultation. 10,21 This is because, compared with gastric ultrasonography, a larger volume of air entering the stomach was required for the gurgling sound to be heard during auscultation. 7,21 On the other hand, the rate of first detection of gastric insufflation using ultrasound was higher in the NM group than in the non-NM group.…”
Section: And Intravenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were similar to those of previous studies that reported that 18-50% of cases of gastric insufflation detected by ultrasonography were missed when using epigastric auscultation. 10,21 This is because, compared with gastric ultrasonography, a larger volume of air entering the stomach was required for the gurgling sound to be heard during auscultation. 7,21 On the other hand, the rate of first detection of gastric insufflation using ultrasound was higher in the NM group than in the non-NM group.…”
Section: And Intravenousmentioning
confidence: 99%
“…10,21 This is because, compared with gastric ultrasonography, a larger volume of air entering the stomach was required for the gurgling sound to be heard during auscultation. 7,21 On the other hand, the rate of first detection of gastric insufflation using ultrasound was higher in the NM group than in the non-NM group. This could be explained by the effect of the neuromuscular blocker.…”
Section: And Intravenousmentioning
confidence: 99%
“…Conventionally, stethoscopic auscultation has been used to evaluate the gastric insufflation during ventilation. Recently, two studies reported that ultrasonography could detect air in stomach more precisely compared with stethoscopic auscultation during facemask ventilation [ 8 , 9 ]. Using real-time ultrasonography, air entry into stomach can be detected with acoustic shadows or comet-tail appearance that appears in the gastric antrum, which provides a qualitative examination of gastric insufflation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies reported that ultrasonography could detect air in stomach more precisely compared with stethoscopic auscultation during facemask ventilation [ 8 , 9 ]. Using real-time ultrasonography, air entry into stomach can be detected with acoustic shadows or comet-tail appearance that appears in the gastric antrum, which provides a qualitative examination of gastric insufflation [ 8 , 9 ]. Recent studies have shown that ultrasonographic measurement of antral cross-section area (CSA) was a quantitative approach to determine gastric insufflation during facemask ventilation [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that many patients with physiologically difficult airways have a greatly reduced tolerance for apnea, and thus consideration should be given to performing a modified RSI with the provision of gentle manual ventilation (<20 cm H 2 O) . Inexpensive disposable in‐line manometers are available for BVMs and their use is recommended to avoid excessive manual ventilation pressures, which can increase the risk of gastric insufflation and regurgitation . Alternatively, avoiding RSI altogether and performing an awake intubation is sometimes the most prudent course of action in the physiologically compromised patient .…”
mentioning
confidence: 99%